IMPLEMENTATION OF TAX DISPUTE SETTLEMENT PROCEDURE THROUGH THE TAX COURT IN SEMARANG - Widiati Dwi Winarni; Mieke Anggraeni Dewi; Mochamad Riyanto (fakultas hukum universitas PGRI Semarang, 2023)
Tax disputes often arise between the fiscus (examiner) and the taxpayer concerned, the authors take the main problem of the source that causes tax disputes and the procedure for resolving tax disputes through the tax court. The method used is a normative legal research method, namely legal research conducted by examining library materials or secondary data supported by primary data found in the field.The Result shows that a Tax dispute is a dispute that arises in the field of taxation between a Taxpayer or Tax insurer and an authorized official as a result of the issuance of a decision that can be appealed or a lawsuit to the Tax Court based on tax laws and regulations, including a lawsuit on the implementation of collection based on the Tax Collection Law. with a warrant. There are 4 causes of tax disputes, namely: (1) Related to laws and regulations; (2) Regarding the application of laws and regulations; (3) Regarding systems, procedures and policies; (4) Regarding the quality of inspection/integrity of the Taxpayer. As for the settlement of tax disputes according to Law Number 14 of 2002 concerning the Tax Court through (1) quasi-judicial (quasi-judicial) or doleansi courts, namely the suspect/defendant of the appeal and lawsuit filed by the Taxpayer is the tax authorities (Director General tax), but also as a determiner who has the authority to decide on the settlement of the said tax dispute; (2) Pure trial in the Tax Court through an appeal or lawsuit from the Taxpayer which is settled by the session of the Tax Court panel.